A complex systems approach for multiobjective water quality regulation on managed wetland landscapes. Issue 6 (27th June 2016) - Parrott, Lael; Quinn, Nigel
Abstract: Management of wetland ecosystems that are tightly coupled with human systems typically requires balancing multiple objectives to ensure that a range of ecosystem services are provided for the benefit of society. We describe how adopting a complex systems approach may provide managers with the appropriate conceptual tools to achieve social and ecological objectives in a multifunctional wetland landscape. We illustrate the applicability of the approach using the Grasslands Ecological Area (GEA) in California as a case study. Human intervention has shaped and reshaped the GEA over the past century, affecting the ability of the landscape to provide ecosystem services. Ecological disaster in the 1980s precipitated transformative change in the management system toward an approach that adopts many of the recommended actions for complexity. Present‐day management, which balances multiple social and ecological objectives, has led to improved water quality, restoration of wetland habitats, and a general increase in system complexity at the landscape scale. New research and real‐time monitoring systems facilitate adaptive management and heterogeneous responses of wetland management entities. We argue that taking a complex systems approach to management in the GEA provides a common, and inclusive, conceptual model for all stakeholders and may lead to a more sustainable and ecologically resilient landscape over the long term.